Downy Mildew of Basil in South Florida - Shouan Zhang; Jaimin S. Patel; Zelalem Mersha; Pamela D. Roberts; Richard Raid (EDIS)
The yellowing of basil leaves could be an indication of the downy mildew of basil disease. This new destructive disease was first detected in south Florida in 2007 and has since spread to at least 42 states in the United States as well as many countries throughout Europe and Africa. This revised 3-page fact sheet describes downy mildew of basil, including its symptoms and ways to control the disease. Written by Shouan Zhang, Jaimin S. Patel, Zelalem Mersha, Pamela D. Roberts, and Richard Raid, and published by the Plant Pathology Department, December 2015.